#TITLE_ALTERNATIVE# - SATRIA (NIM 13204204), ANDRI
Study about double three-phase motor-based electric mover is presented in this final report. In this research several kinds of induction motor-based mover are compared. The study begins with analysis of current ripples in the input side and rotor. It is found that in the application of square wave inverter, the configuration of double three-phase induction motor with 30o phase shift is better than the one with 0o phase shift. Otherwise, in the application of PWM inverter, double three-phase induction motor with 0º phase shift is better. The simulation using Simulink is also presented to verify the analyzing results.